Screening the adequacy of hydroxychloroquine prescription and monitoring of ocular toxicity in patients with rheumatic disease - Khan, Saira Elaine Anwer; Aslam, Muhammad Zeeshan; Khan, Asadullah; Din, Zia ud; Bashir, Farhan; Khan, Hajra (Journal of Fatima Jinnah Medical University, 2020)
Background: Hydroxychloroquine (HCQ) an anti-inflammatory drug used in treatment of rheumatic diseases causes retinal toxicity in a minority of patients which are both time and dose dependent. The aim of this study was to assess the compliance with guidelines of American Association of Ophthalmology for screening and dosage of this drug. Patients and methods: In this cross-sectional analysis, the medical records of patients who were on HCQ, attending Rheumatology Outpatient Department of Fatima Memorial Hospital Shadman, Lahore from 25-05-2019 to 30-05-2019 were reviewed. The dosage and, duration of HCQ were collected, files were reviewed for physician recommendation of screening tests for retinal toxicity. HCQ dose of 5mg/kg/day was labeled as adequate dose; dose below 4.5mg/kg/day under dosed, while dose of 6mg/kg/day and above was considered overdose. Results: Data was collected from 81 patients during the study period, 74 (91.4%) of them being female, with mean age 35.15 ± 12.6 years. Based on total body weight, 23 patients (28.4%) were receiving the correct dosage of the drug around 5mg/kg/day whereas 39 (48.1%) patients were under-dosed below 4.5mg/kg/day, and 19 patients (23.5%) were over dosed, out of which 5 (6.17%) were receiving doses above 6.5mg/kg. Baseline eye screening examination by ophthalmologist was performed within 1 year of commencing treatment in 54 (66%) patients. Of the 27 patients receiving HCQ more than 5 years, 6 patients underwent Spectral coherence Ocular CT scan (SD-OCT) evaluation at 5 years. There was minimal compliance (less than 70% of Patients) to optimum drug dosage, partial compliance (70-89% patients) to preventing over-dosage of the drug, and full compliance (more than 90% patients) was achieved in baseline screening exam recommendation. Follow-up screening documentation and 5-years screening examination had minimal compliance. Conclusion: A significant proportion of patients are underdosed, especially the obese population where the recommended dosage is not prescribed.